Infant Social Withdrawal Behavior: A Key for Adaptation in the Face of Relational Adversity - Viaux-Savelon, Sylvie; Guedeney, Antoine; Deprez, Alexandra (Frontiers in Psychology, 2022)
As a result of evolution, human babies are born with outstanding abilities for human communication and cooperation. The other side of the coin is their great sensitivity to any clear and durable violation in their relationship with caregivers. Infant sustained social withdrawal behaviour (ISSWB) was first described in infants who had been separated from their caregivers, as in Spitz’s description of ‘hospitalism’ and ‘anaclitic depression’. Later, ISSWB was pointed to as a major clinical psychological feature in failure-to-thrive infants. Fraiberg also described freezing behaviour as one of the earliest modes of infant defence in the face of adverse situations threatening the infant’s ability to synchronize with caregivers. We hypothesise that ISSWB behaviours are associated with poor vagal brake functioning and that an impaired social engagement system is induced by an impoverished and/or dangerous environment. Recent research using animal models highlight the neurobiology and the genetics of the social Approach/Withdrawal Behaviour in infants. The present paper is therefore a plea for social withdrawal behaviour to be attributed a more important role as a major psychological defensive mechanism in infancy, and for research into early development and early intervention to make more practical and theoretical use of this concept, thus decreasing the challenge of translation in social neurosciences. This work presents several situations involving developmental hazards in which assessment of ISSWB by means of the Alarm Distress Baby Scale (ADBB) has proven useful, i.e. malnutrition, effects of major maternal depression and or traumatization, assessing social withdrawal in infants with an chronic organic illness (congenital heart disease, Prader- Willi syndrome, cleft lip and/or palate Prader-Willy syndrome, Foetal alcohol syndrome) or assessing ISSWB in out of home placed infants during parental visitation. Relationships between ISSWB and other biophysiological behavioural systems are discussed, particularly links with attachment processes and Porges’s polyvagal theory.